Epidural Analgesia and Postoperative Lipid Metabolism: Stable Isotope Studies During a Fasted/Fed State. Issue 2 (1st March 2002) - Carli, F.; Lattermann, R.; Schricker, T.
Abstract : Background and Objectives: Although previous studies have reported an inhibitory effect of epidural block and glucose feeding on plasma concentrations of glycerol and free fatty acids (FFA), it remains unclear how epidural analgesia modifies the postoperative production and uptake of lipid metabolites. This can be achieved by determining the rate of lipolysis during a feeding state with dextrose. Methods: Twelve patients with or without postoperative epidural analgesia were studied 48 hours after surgery. They underwent a 6-hour stable isotope infusion study using [1, 1, 2, 3, 3, - 2 H5 ] glycerol; 3 hours of fasting, and 3 hours of dextrose infusion (4 mg/kg/min). The rate of glycerol appearance (Ra glycerol) i.e., rate of lipolysis, and plasma concentrations of glycerol, FFA, glucose, lactate, insulin, glucagon, and cortisol were measured during the fasted and the fed states. Results: The rates of lipolysis were similar in both groups during the fasted state and were not modified by dextrose infusion. In contrast, plasma concentrations of glycerol and FFA were decreased significantly during the fed state ( P < .01). Glycerol clearance (ratio between Ra glycerol and plasma glycerol concentration) increased significantly in both groups ( P < .05) with feeding. Similarly, plasma concentrations of glucose and insulin increased significantly following feeding with dextrose in both groups. Conclusions: The elevated rates of lipolysis associated with surgery cannot be suppressed by either epidural analgesia or dextrose feeding implying that the sustained stress response continues in the postoperative period and is the most important factor responsible for the increased release of glycerol.